Proposing an LCA methodology for the assessment of neighbourhood refurbishment measures. (13th March 2023) - Slabik, Simon; Storck, Michael; Zernicke, Caya; Hafner, Annette
Abstract: Environmental impacts of new construction in the built environment have been determined for considerable time using life cycle assessments (LCAs). However, the significance of the existing building stock is neglected when considering environmental impacts at the level of embodied energy. Today alone, most of the buildings that will remain in place in 2050 are already in existence. For achieving national and international climate protection goals, the LCA of refurbishment measures is crucial. Thus, the link between building LCAs, which are conducted based on EN 15978, and refurbishment measures is established and ultimately transferred to the neighbourhood level. This paper provides a methodology in accordance with applicable standards to make use of a large activation potential in neighbourhoods. An initial focus is on the survey of the area to be investigated. The subdivision and typologisation of the building stock based on established toolboxes within the neighbourhood as well as the description of the implemented measures are besides in the focus of the methodology. Multiple scenarios for existing buildings in the neighbourhood combined with a consistent framework enables LCA to be conducted. The connection of the spatial component by a demarcated neighbourhood and the connection with the structural dimension by buildings enables a holistic view of refurbishment measures in the urban environment. As a link between the individual building and the municipality, the neighbourhood serves as a meso level.